Pengaruh Firm Size, Subsidiaries, Auditor Size, Loyalitas, dan External Audit Report Lag terhadap Audit Fee: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Candra Indriyanti Putro; Noer Sasongko (Penerbit Goodwood, 2023)
Purpose: This study aims to analyze the effect of firm size, subsidiaries, auditor size, loyalty, and external audit report lag on audit fees in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Methodology/approach: The population of this study are manufacturing companies listed on the IDX with an observation period of 2018-2020. The research sample consisted of 30 companies from 56 saturated samples determined by purposive sampling technique. The data analysis technique used is multiple linear regression with the help of the SPSS program. Results/findings: The results of the study concluded that partially firm size, auditor size, and loyalty variables affect the audit fee. Meanwhile, the variables of subsidiaries and external audit report lag have no effect on audit fees for manufacturing companies listed on the Indonesia Stock Exchange. Limitation: in manufacturing companies in the consumer goods industry sector only. The limitation of this research is that the research object is not extensive, only exists, so a small sample is obtained. Contribution: This research is useful as information material and for regulators' considerations to provide clearer regulations and explanations related to the determination of audit fees, so that the information obtained is transparent so that it makes it easier for investors to make decisions. It is hoped that with regulations and supervision regarding the amount of the audit fee, relevant information can be obtained.